THE ANALYSIS OF EFL LEARNERS’ SELF-CONFIDENCE TO AFFLUENCE THE UNCOMMUNICATIVENESS IN SPEAKING SKILL - Renaldi, Ikrar Genidal (Universitas Borneo Tarakan, 2020)
This study deals to increase the English as a Foreign Language (EFL) students' confidence in English speaking. This research used qualitative analysis by distributing questioner. This study suggest that EFL teachers should seek ways to increase students' collaboration in the classroom to help them gain confidence in speaking. The study involved the students in the fifth semester (class 1) in the English Department in the 2018/2019 academic year, Tidar University. The researcher compared the gathered data with other relevant researches and theories involved in the study. Based on the research questions, the research result shows that students’ perceptions of self-confidence have a significant to decrease reticence in speaking skills. However, lecturers need to push the students in practice speaking English in front of a class, especially to improve the self-confidence when the students are communicating in English. Two research questions were formulated in this study. There are: (1) what are the factors of the EFL students’ reticence in speaking? (2) Do the students have high self-confidence in speaking skills?